2017
DOI: 10.1002/rcs.1814
|View full text |Cite
|
Sign up to set email alerts
|

Early experience of laparoscopic and robotic hybrid pancreaticoduodenectomy

Abstract: Hybrid PD is feasible and safe. The learning curve of hybrid surgery, particularly robotic anastomosis, is relatively short.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…It is debatable whether the superior approach for PD is totally robotic surgery or laparoscopic/robotic hybrid surgery. Fernandes et al reported that a totally robotic approach was superior, whereas other studies reported that a hybrid laparoscopic and robotic approach consisting of laparoscopic dissection and robotic reconstruction was superior . The present study used a hybrid approach; laparoscopic surgery enabled a prompt response and wide range of motion during the dissection phase, while robotic surgery enabled fixed and fine movement during the anastomosis phase.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…It is debatable whether the superior approach for PD is totally robotic surgery or laparoscopic/robotic hybrid surgery. Fernandes et al reported that a totally robotic approach was superior, whereas other studies reported that a hybrid laparoscopic and robotic approach consisting of laparoscopic dissection and robotic reconstruction was superior . The present study used a hybrid approach; laparoscopic surgery enabled a prompt response and wide range of motion during the dissection phase, while robotic surgery enabled fixed and fine movement during the anastomosis phase.…”
Section: Discussionmentioning
confidence: 76%
“…In the present study, the mean operation time in the robot PD group was 335.6 ± 69.4 min. According to our early experience with 16 patients, the mean operation time was 414.7 ± 47.1 min . Therefore, as more cases were experienced, the operation time was reduced.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 However, this study precluded randomised controlled trials 10,11 and several other important cohort studies, limiting validity of their review. [16][17][18][19][20] Hence, this systematic review aims to comprehensively evaluate all current and relevant evidence and perform a network meta-analysis to identify techniques associated with superior peri-operative outcomes in patients undergoing PD using a similar methodology to a recent publication on distal pancreatectomy. 21 In order to include a broader spectrum of surgical approaches, this review will summarise findings of both randomised and non-randomised studies.…”
Section: Introductionmentioning
confidence: 99%